POTENTIAL DEMAND ANALYSIS OF LRT BANDUNG RAYA AS URBAN TRANSPORTATION MODE (CASE STUDY: BABAKAN SILIWANGI â LEUWIPANJANG â SOREANG) - Harianti Asri Dewi, R
Metropolitan Bandung Raya is a National Strategic Area. Along with population and economic growth in this area resulting high mobilization which need facilities and infrastructure supporting. This condition has an impact on increasing the number of vehicles and cause congestion, especially during rush hour on the north - south Bandung route. Currently, the MBR area required that there be development of an urban transportation system. One of the transportation systems developed is a mass transportation system that can accommodate movement within the city. This study compares four alternative modes: LRT, existing public transportation, paratransit (taxi), and private vehicles (cars). While the motorcycle and taxibike are not included in the alternative modes of choice, because they have lower costs and faster travel times, so these modes are always superior in choosing as urban modes. This study aims to identify factors that influence mode choice preferences by using the multinomial logit method in biogeme application. The resulting model has a power level of 41.6%. Factors that influence mode choice preferences are travel time, distance to the station, number of transfers (1 time), number of transfers (2 times), waiting time (PR), age, education (not graduated high school), education (undergraduate S1/D4), occupation (BUMN/BUMD), bicycle ownership (1 unit), existing travel time, walking distance (km), reason (fast travel time), reason (no other alternative), public transportation transfer (1 time), and egress distance (km). The probabilities generated for each mode are LRT (67%), existing public transport (6%), paratransit (3%), and private vehicles (24%). These show that there is a potential demand for LRT alternative mode as a mode of urban transportation in Greater Bandung, especially on the Babakan Siliwangi – Leuwipanjang – Soreang route for people who have close access to the LRT station.